The safety and health of workers in the Malaysian wooden furniture industry : an assessment of noise and chemicals solvents exposure. - Ratnasingam, Jegatheswaran; Ioras, F. (Asian Network for Scientific Information, 2010)
This study was carried out to evaluate the noise and chemical solvents exposure among workers in the wooden furniture industry in Malaysia. Portable noise-level measurements showed that the rough-milling operations recorded the highest noise-level in the furniture factories. Personal dosimeter measurement results showed that 43% of the workers were exposed to noise-levels higher than the permissible limit, while audiometric tests revealed that 34.7% of the workers suffered from hearing handicap, hence strongly recommending the use of noise protection gadgets among workers. As for the chemical solvents, the study found that the current exposure levels for both chemical solvents and formaldehyde in the Malaysian wooden furniture industry were higher than the Permissible Exposure Levels (PEL). Hence, workers in the surface coating departments must be provided with masks with filters, to ensure their exposure to chemical solvents are minimized. This study also revealed that despite the existent of occupational health and safety regulations in Malaysia, its implementation and enforcement within the wooden furniture industry must be improved to ensure the workers safety and health.